Populists at work: Italian municipal finance under M5S governments - Massimo Bordignon; Tommaso Colussi; Francesco Porcelli (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2024)
This paper empirically investigates the impact of populist governments on public policies and finances. We focus on Italian local governments (i.e. municipalities) over the 2010-2019 period, when a populists, i.e. the Five Stars Movement, became the most voted party in the country. We first document that the re-election probability of incumbent mayors drops by half when they are populist. While populist mayors are not less qualified than mainstream parties, they are significantly younger and less experienced. Estimates from a stacked diff-in-diff design comparing early to not-yet treated municipalities show that the populist government experience significantly worsen municipal finances. Populist mayors also fail to promote social and environmental policies that align with the political demands of their voters, possibly contributing to their difficulties in securing re-election.
Keywords: H70; H72; P43; 330; Populism; Local Governments; Fiscal Policy; Inequality